2014
DOI: 10.1364/ao.53.000b53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of symbol modulation coding on readout fidelity of shift-multiplexed holographic digital data page storage in a photopolymerizable nanoparticle-(thiol-ene)polymer composite film

Abstract: We report on shift-multiplexed holographic storage of 250 digital data pages in a photopolymerizable SiO₂ nanoparticle-polymer composite film being capable of step-growth thiol-ene polymerization in the green. Various two-dimensional symbol modulation codes for the digital data page format were employed to examine the dependence of the readout fidelity on modulation coding schemes. It is found that, as compared to 1:2 and 2:4 modulation codes, higher-order 5:9, 9:16, and 13:25 modulation codes possessing reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…To further mitigate polymerization shrinkage occurring in NPC films during recording, Hata et al [ 73 75 ], and Mitsube et al [ 76 ] proposed the use of TE and TY photopolymerizations that proceed via a step growth radical addition mechanism for volume holographic recording in NPCs. Using such a new NPC system, Momose et al demonstrated holographic shift multiplexing of more than one hundred 2D digital data pages with high fidelity readout [ 78 , 79 ]. This demonstration will be described in Section 4.1 .…”
Section: Photopolymerizable Npc Systems and Their Holographic Recordimentioning
confidence: 99%
See 3 more Smart Citations
“…To further mitigate polymerization shrinkage occurring in NPC films during recording, Hata et al [ 73 75 ], and Mitsube et al [ 76 ] proposed the use of TE and TY photopolymerizations that proceed via a step growth radical addition mechanism for volume holographic recording in NPCs. Using such a new NPC system, Momose et al demonstrated holographic shift multiplexing of more than one hundred 2D digital data pages with high fidelity readout [ 78 , 79 ]. This demonstration will be described in Section 4.1 .…”
Section: Photopolymerizable Npc Systems and Their Holographic Recordimentioning
confidence: 99%
“…As described in Section 3.1.2 , volume gratings recorded in the TE-based NPC incorporating inorganic nanoparticles satisfy these requirements [ 73 , 74 ], suggesting their use for HDS media. Indeed, it was shown that TE-based NPCs gave good performance in shift-multiplexed holographic digital data page storage [ 78 , 79 ].…”
Section: Holographic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Using such thiol-ene based NPCs at the stoichiometric thiol-to-ene ratio, we showed shrinkage reduction below 0.5% with Dn sat as large as 1 Â 10 À2 and S higher than a) Electronic mail: ytomita@uec.ac.jp 0021-8979/2015/117(5)/053105/6/$30.00 V C 2015 AIP Publishing LLC 117, 053105-1 Furthermore, we used such thiol-ene based NPCs as greensensitized HDS media to demonstrate the excellent performance in holographic shift multiplexing of more than 200 of 2D digital data pages with high fidelity. 32,33 The thiol-ene photopolymerization mechanism was also used to record electrically switchable reflection gratings in holographic polymer-dispersed liquid crystals at Ar-ion and solid-state laser lines of 364, 442, 488, and 532 nm. 31,[34][35][36] Thanks to the recent development of highly coherent blue diode lasers for HDS, 37 it is possible to implement compact HDS systems in the blue (at and near the 405-nm diode laser line).…”
Section: Introductionmentioning
confidence: 99%